Pengaruh Stimulus Kutaneus Slow-Stroke Back Massage Terhadap Skala Nyeri Dismenore Primer Pada Mahasiswi Stikes Amanah di Padang : The Effect of Cutaneous Stimulus Slow-Stroke Back Massage on Primary Dysmenorrhea Pain Scale in Student of Stikes Amanah in Padang - Vetty Priscilla; Esi Afriyanti (NERS Jurnal Keperawatan, 2017)
Puberty in girls is indicated by a menstruation. Each adolescent girls have a different experience of their periods. Some girls get period without any complaints, but some of them accompanied with dysmenorrhea which resulted in a sense of discomfort in the form of pain that can interfere their daily activities. According to AHCPR (Agency for Health Care Policy and Research), pain management that can be performed by nurses are nonpharmacological therapy, one of which is cutaneous stimulation, Slow-Stroke Back Massage. This study aimed to investigate the direct effect of cutaneous stimulus: Slow-Stroke Back Massage on primary dysmenorrhea pain scale. Design for this reasearc is a quasi experiment in one group (one group pre test- post test design). Subjects in this study were 12 female nursing students of Stikes Amanah Padang who have met criteria of the study. Subjects had been taught about technique of slow-stroke back message, and practice during their period when dysmenorrhea felt for 1 week. Previously, pain experience during menstruation assessed using a scale Numerical Rating Scales (NRS). Data were analyzed using paired t-test. This study showed that more than half of female students (75%) were experienced a moderate level of dysmenorrhea pain with pain scale was 5.67 ± 1.56 before being given cutaneous stimulus slow-stroke back massage (pretest). After given the slowstroke back message (posttest), more than half (58.2%) experienced a mild level of pain dysmenorrhea with pain scale was 4 ± 2.09. The cutaneous stimulus slow-stroke back message can reduce dysmenorrhea pain scale of nursing students in STIKes Amanah Padang.